NCTUns 4.0: An integrated simulation platform for vehicular traffic, communication, and network researches - Wang, S. Y.; Chou, C. L.; Chin, Y. H.; Tzeng, Y. S.; Hsu, M. S.; Cheng, Y. W.; Liu, W. L.; Ho, T. W. (My University, 2007)
In this paper, we present an integrated simulation platform, called NCTUns, for vehicular traffic, communication, and network researches. This platform combines the capabilities supported by a network simulator and those supported by a traffic simulator. With these simulation capabilities, NCTUns can be used to design protocols for Intelligent Transportation Systems (ITS) communication networks such as a wireless vehicular communication network. Besides, the novel architecture of the platform enables the real-world Linux protocol stack and any real-world application to be used in simulations of such networks. In this paper, we present the design of NCTUns for supporting ITS researches and show its scalability.